1983
DOI: 10.1111/j.1464-410x.1983.tb03326.x
|View full text |Cite
|
Sign up to set email alerts
|

ABO, MNSs and Rhesus Blood Groups in Bladder Cancer

Abstract: Data are presented on a group of cases of primary carcinoma of the bladder detailing their ABO, MNSs and rhesus blood antigenic phenotypes. Differences, either between all cases and controls or between particular stages of presentation and controls, have been found in the ABO red cell system as well as the MNSs red cell system. In the case of the ABO system an excess of the A gene is present but detailed study shows this to be only in patients with T1 and T2 tumours. No excess was seen in patients with carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In a number of studies concerning bladder cancers additional prognostic factors have been investi gated among blood group antigens. An excess of the A gene has been demonstrated although others have shown that the excess of the A gene was limited to patients with T1 and T2 tumors [4], Patients with blood group A had lower grade tumors with lower mortality rates compared to patients with blood group O [5] in accordance with another study [6] in which the progression to advanced disease was significantly greater among those with blood group O and superficial and low grade tumors.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a number of studies concerning bladder cancers additional prognostic factors have been investi gated among blood group antigens. An excess of the A gene has been demonstrated although others have shown that the excess of the A gene was limited to patients with T1 and T2 tumors [4], Patients with blood group A had lower grade tumors with lower mortality rates compared to patients with blood group O [5] in accordance with another study [6] in which the progression to advanced disease was significantly greater among those with blood group O and superficial and low grade tumors.…”
Section: Introductionsupporting
confidence: 73%
“…The apparent excess of the A gene seen among bladder cancers [4] was also found in this study of UUTT although only further studies can verify this trend or dis close whether this in fact is due to a lack of O genes. Staging and grading of dysplasia affords optimal con ditions following treatment of UUTT because the tumors or more commonly the whole organs are resected by way of nephrourcterectomy providing adequate material for histopathological examination.…”
Section: Discussionmentioning
confidence: 54%
“…Srinivas et al [13] supposed that though the etiology of such a tendency was still unknown, it was possibly correlated to the loss of surface antigens. In a study of 288 patients with primary bladder tumor, Cartwright et al [ 14] found that most of the type A blood group patients suffered from early stage tumors (clinical stage T1 and T2), while group O patients had late stage tumors (clinical stage T3 and T4). In their conclusion, they suggested that the group A glycoprotein differentially inhibits or restricts the invasive potential of cells, whereas due to the lack of such function, blood group O appears to display a trend towards invasive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There were many predictive methods of evaluat ing the invasive potentials. In addition to grades and stages, the indirect immunoperoxidase test to detect uro-thelial cell surface blood group antigens has been used for this purpose [15,16], Also N-acetyltransferase status [17], DNA/RNA ratio [18], and chromosomes [19] have been analyzed for evaluating the invasiveness of superfi cial bladder cancer. However, no methods should be def initely applied using these criteria.…”
Section: Discussionmentioning
confidence: 99%